Highly Emissive Layers based on Organic/Inorganic Nanohybrids Using Aggregation Induced Emission Effect. Issue 1 (12th September 2021) - Phelipot, Jonathan; Ledos, Nicolas; Dombray, Thomas; Duffy, Matthew P.; Denis, Mathieu; Wang, Ting; Didane, Yahia; Gaceur, Meriem; Bao, Qinye; Liu, Xianjie; Fahlman, Mats; Delugas, Pietro; et al.
Abstract: Fluorescent nanohybrids, based on π‐extended hydroxyoxophosphole ligands grafted onto ZnO nanoparticles, are designed and studied. The restriction of the intramolecular motions of the organic fluorophore, through either aggregates' formation in solution or processing into thin films, forms highly emissive materials due to a strong aggregation induced emission effect. Theoretical calculations and XPS analyses were performed to analyze the interactions between the organic and inorganic counterparts. Preliminary results on the use of these nanohybrids as solution‐processed emissive layers in organic light emitting diodes (OLEDs) illustrate their potential for lighting applications. Abstract : Novel fluorescent nanohybrids, based on π‐extended hydroxyoxophosphole ligands grafted onto ZnO surface, are found to form highly emissive materials due to a strong aggregation induced emission effect, through either aggregates' formation in solution or processing into thin films. The use of these nanohybrids as solution‐processed emissive layers in organic light emitting diodes (OLEDs) highlights their potential for lighting applications.